Regulation of Motivation to Self-Administer Ethanol by mGluR5 in Alcohol-Preferring (P) Rats - Besheer, Joyce (2007)
BACKGROUND: Emerging evidence indicates that Group I metabotropic glutamate receptors (mGluR1 and mGluR5) differentially regulates ethanol self-administration in several rodent behavioral models. The purpose of this work was to further characterize involvement of Group I mGluRs in the reinforcing effects of ethanol using a progressive ratio schedule of reinforcement. METHODS: Alcohol-preferring (P) rats were trained to self-administer ethanol (15% v/v) versus water on a concurrent schedule of reinforcement, and the effects of the Group I mGluR antagonists were evaluated on progressive ratio performance. The rats were then trained to self-administer sucrose (0.4% w/v) versus water, and the effects of the antagonists were tested on progressive ratio performance. RESULTS: The mGluR1 antagonist, 3,4-dihydro-2H-pyrano[2,3]b quinolin-7-yl (cis-4-methoxy-cyclohexyl) methanone (JNJ 16259685; 0 to 1 mg/kg) and the mGluR5 antagonist, 6-methyl-2-(phenylethynyl) pyridine (MPEP; 0 to 10 mg/kg) dose-dependently reduced ethanol break point. In separate locomotor activity assessments, the lowest effective dose of JNJ 16259685 (0.3 mg/kg) produced a motor impairment, whereas the lowest effective dose of MPEP (3 mg/kg) did not. Thus, the reduction in ethanol break point by mGluR1 antagonism was probably a result of a motor impairment. JNJ 16259685 (0.3 mg/kg) and MPEP (10 mg/kg) reduced sucrose break point and produced motor impairments. Thus, the reductions in sucrose break point produced by both Group I antagonists were probably because of nonspecific effects on motor activity. CONCLUSIONS: Together, these results suggest that glutamate activity at mGluR5 regulates motivation to self-administer ethanol.